Towards an Integrated Islamic Curriculum for Bangladesh in line with the Recommendations of OIC Conference'77 (IIUC Studies, 2015)
Education holds very high position in Islam, the 1st revelation to the Prophet (s.a.w.) contains especial emphasis on knowledge and has been identified as an especial favour of the Creator. The four point objectives behind sending the Prophet Muhammad (s.a.w) with the mission of prophethood are all related to recitation, teaching and purification of soul through continuous training and guidance. Seeking knowledge has been made an obligatory duty on every Muslim - male and female - by the Prophet (s.a.w.). The Muslim wherever had ruled they had patronized education and established educational Institutions. These were open to all the peoples regardless of race, religion and caste. The Muslim rulers who ruled Bengal for more than 500 years had established many educational institutions, introduced a very advanced education system in Bengal, which was Islamic in nature and an integrated policy based on Arabic and Persian. After the British took over the rule of Bengal from the hands of the Muslims, they introduced an English medium secular education policy replacing the prevailing education system introduced by the Muslims. But the majority of the Muslims could not accept that policy, knowing that the main objective behind introducing that policy was degrading the Muslim society. The paper is a historical overview of prevailing Curriculum of the Islamic Education System in Bengal and the then East Pakistan in general, and the present Bangaldesh in particular in one hand, and a recommendation for introducing an integrated Islalmic Education Policy on the other.IIUC Studies Vol.9 December 2012: 17-38